Study on the influencing factors of shear strength of loess mudstone interface - Xuancheng Ren; Shijie Liu; Tao Zhu; Bowen Xu (PLoS ONE, 2026)
In Loess Plateau, low shear strength of the loess–mudstone contact interface leads to the loess–mudstone landslides. However, the influencing factors of shear strength of loess-mudstone interface and the disaster-causing effect of interface landslide are not clear. Therefore, this study focus on the loess-mudstone interface, and conducts direct shear tests under different water content, density and morphology conditions. The results show that the shear strength of loess-mudstone interface is always lower than that of homogeneous loess and mudstone. An increase in moisture content leads to a continuous reduction in shear strength, whereas an increase in dry density enhances shear strength. A decrease in interface roughness also results in a reduction in shear strength parameters. Specifically, when interface roughness decreases from 1.72 to 0, cohesion decreases by 42%, and friction angle decreases by 13%. The failure modes in different interface types can be classified into three: interface shear, locked-segment, and partial locked-segment failure model. This study analyzes the influencing factors and internal mechanism of shear strength of loess-mudstone interface, reveals its landslide disaster effect, and puts forward suggestions for risk assessment of loess-mudstone landslide. The results are of great value to the potential risk assessment of loess-mudstone landslide.